PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. ISS INDONESIA CABANG MEDAN - ELVIE MARIA; MAY HANDRI; ADE PURNAMA (JURNAL ILMIAH MAKSITEK, 2019)
This study aims to see the influence of organizational culture and work motivation toward employee job satisfaction . This research uses quantitative research methods. The population in this study were 132 employees of PT. ISS Indonesia, Medan Branch. Sampling techniques using the Slovin formula and obtained as many as 99 employees. Data analysis techniques using the classic assumption test, multiple linear regression, t test, F test, and the coefficient of determination (r2). The results showed that partially, organizational culture and work motivation had a positive and significant effect on job satisfaction. Simultaneously, organizational culture and work motivation affect job satisfaction by 80.3%. while the remaining 19.7% is explained by the influence of other factors or variables outside the model not discussed in this study